Lemon - Kwŏn, Yŏ-sŏn, 1965- (Other Press, 2021)
"In this piercing psychological portrait that takes the shape of a crime novel, a woman haunted by her sister's unsolved murder transforms herself in order to cope with the pain of absence and unknowing. In the summer of 2002, when Korea is abuzz over hosting the FIFA World Cup, nineteen-year-old Kim Hae-on is killed in what becomes known as the High School Beauty Murder. Two suspects quickly emerge: rich kid Shin Jeongjun, whose car Hae-on was last seen in, and delivery boy Han Manu, who witnesses Hae-on in the passenger seat of Jeongjun's car just a few hours before her death. But when Jeongjun's alibi turns out to be solid, and no evidence can be pinned on Manu, the case goes cold. Seventeen years pass without any resolution for those who knew and loved Hae-on, and the grief and uncertainty take a cruel toll on her younger sister, Da-on, in particular. Unable to move on with her life, Da-on tries in her own twisted way to recover some of what she's lost, ultimately setting out to find the truth of what happened. Told at different points in time from the perspectives of Da-on and two of Hae-on's classmates, Lemon loosely follows the structure of a detective novel. But finding the perpetrator is not the main objective here. Instead, the work explores grief and trauma, raising important questions about guilt, retribution, and the meaning of death and life"--